How do you solve #3(3t + 3) = 3(-3t + (-39))#?

1 Answer
Jul 23, 2015

Answer:

You isolate all the terms that contain #t# on one side of the equation.

Explanation:

So, start by looking at your starting equation

#3 * (3t + 3) = 3 * [-3t + (-39)]#

This is equivalent to

#cancel(3) * (3t + 3) = cancel(3) * (-3t - 39)#

To get all the terms that contain the variable #t# on one side of the equation, add #3t# on both sides to get

#3t + 3 + 3t = cancel(-3t) + cancel(3t) - 39#

#6t + 3 = -39#

Now add #-3# on both sides of the equation to isolate the term that contsins #t# on one side

#6t + cancel(3) + cancel(-3) = -39 - 3#

#6t = -42#

This means that #t# is equal to

#t = -42/6 = color(green)(-7)#